Tubulocystic renal cell carcinoma: Report of a rare case - Kakkar, Aanchal; Sharma, Mehar C.; Uppal, Manpreet; Chumber, Sunil (Canadian Urological Association Journal, 2015)
Cystic neoplasms of the kidney are rare, and present a unique diagnostic challenge. We report the case of an elderly male who presented with a large cystic neoplasm, which was a diagnostic dilemma clinically and radiologically. Histopathological examination showed a tumour composed of variably sized tubules lined by atypical cells having large round nuclei with prominent nucleoli. Hobnailing was seen at places. Tumour cells were immunopositive for pancytokeratin, vimentin, CD10, CK19 and AMACR, confirming a diagnosis of tubulocystic renal cell carcinoma (TC-RCC).